Image quality and diagnostic accuracy of a handheld nonmydriatic fundus camera: Feasibility of a telemedical approach in screening retinal diseases. Issue 10 (1st October 2020) - Lin, Tai-Chi; Chiang, Yueh-Hua; Hsu, Chih-Lu; Liao, Long-Sheng; Chen, Yi-Ying; Chen, Shih-Jen
Abstract : Background: A suitable fundus camera for telemedicine screening can expand the scale of eye care service. The purpose of this study was to compare a handheld nonmydriatic digital fundus camera and a conventional mydriatic fundus camera according to the image quality of their photographs and usability of those photographs to accurately diagnose various retinal diseases. Methods: A handheld nonmydriatic fundus camera and conventional fundus camera were used to take fundus photographs of outpatients at an ophthalmic clinic before and after pupillary dilation. Image quality and diagnostic agreement of the photos were graded by two masked and experienced retinal specialists. Results: A total of 867 photographs of 393 eyes of 200 patients were collected. Approximately 80% of photos taken under nonmydriasis status using the handheld nonmydriatic fundus camera had good (55.7%) or excellent (22.7%) image quality. The overall agreement of diagnoses between the doctors was more than 90%. When the handheld nonmydriatic fundus camera was used after mydriasis, the proportion of images with good (45%) or excellent (49.7%) quality reached 94.7% and diagnostic agreement was 93.4%. Lens opacity was associated with the quality of images obtained using the handheld camera ( p = 0.041), and diagnosis disagreement for handheld camera images was associated with preexisting diabetes diagnosis ( p = 0.009). Approximately 40% of patients expressed preference for use of the handheld nonmydriatic camera. Conclusion: This study demonstrated the effectiveness of the handheld nonmydriatic fundus camera in clinical practice and its feasibility for telemedicine screening of retinal diseases.